Spatial differentiation of gated communities in Nanjing. Issue 3 (2nd September 2017) - Song, Weixuan; Liu, Chunhui
ABSTRACT: Since market reform began in China's housing sector, gated communities have been the mainstream model for newly built residential communities. There is a rich literature exploring the popularity and social-spatial effects of gated communities, as well as reactions to them. However, the general layout and spatial differentiation of gated communities in urban areas have been scarcely explored. This paper studies the central urban area of Nanjing, which was determined in the Urban Master Planning of Nanjing ( 2011–2010 ). The research object is the set of 1114 gated communities that were built after 1998. The Theil Index and GIS Contour Line are used to analyse the spatial distribution of housing prices, property management fees and plot ratios of these gated communities in Nanjing. Then, we reveal the spatial differentiation of the types and grades of the gated communities and propose a spatial differentiation model of gated communities in Nanjing. Based on all of the above, this paper also discusses how factors including location/land price, city planning, construction type, resource allocation, and year of establishment impact the gated communities' spatial differentiation and how the gated communities' spatial differentiation reflects and predicts urban socio-spatial differentiation.